Providing maceration protocols for xylem and phloem research - Romero, Eunice; Olson, Mark; Segovia-Rivas, Alí; Pittermann, Jarmila; Jupa, Radek (Frontiers in Plant Science, 2026)
Maceration technique allows isolating and studying the structure of plant cells, providing essential insights into plant physiology and responses to environmental factors. Despite its importance, the methods sections of publications often lack sufficient detail to properly apply maceration technique, preventing broader applications beyond industrial and wood identification studies. Here we describe maceration protocols (P), as guidelines, to allow successful cell separation, in woody and herbaceous plants, for further studying the structure of vascular tissues (xylem and phloem), using Franklin’s solution instead of the traditional, more toxic Jeffrey’s. We included sample preparation, equipment and chemicals, recommended stains and means of slide preparation that ensure clear observation and imaging, and identified potential pitfalls and safety practices. P1 provides a simple xylem and phloem maceration technique, with non-permanent slides preparation, suitable for observation under light, fluorescence or confocal microscopy. P2 and P3 are suitable for producing permanent slides of macerated xylem cells. P2 has been successfully used for macerating xylem of angiosperms and gymnosperms from at least 34 families and 25 orders, with densities ranging widely. P3 uses minimal substances and time for dehydration and staining. These flexible protocols may contribute to unlocking the potential of maceration technique to advance research in ecology and evolution.